The involvement of multiple thrombogenic and atherogenic markers in premature coronary artery disease - Antonio P. Mansur; Julio Y. Takada; Celia M. C. Strunz; Solange D. Avakian; Luiz Antonio M. Cesar; Jose A.F. Ramires (Clinics, 2013)
OBJECTIVE: To examine the association of atherogenic and thrombogenic markers and lymphotoxin-alfa gene mutations with the risk of premature coronary disease. METHODS: This cross-sectional, case-control, age-adjusted study was conducted in 336 patients with premature coronary disease (<50 years old) and 189 healthy controls. The control subjects had normal clinical, resting, and exercise stress electrocardiographic assessments. The coronary disease group patients had either angiographically documented disease (>50% luminal reduction) or a previous myocardial infarction. The laboratory data evaluated included thrombogenic factors (fibrinogen, protein C, protein S, and antithrombin III), atherogenic factors (glucose and lipid profiles, lipoprotein(a), and apolipoproteins AI and B), and lymphotoxin-alfa mutations. Genetic variability of lymphotoxin-alfa was determined by polymerase chain reaction analysis. RESULTS: Coronary disease patients exhibited lower concentrations of HDL-cholesterol and higher levels of glucose, lipoprotein(a), and protein S. The frequencies of AA, AG, and GG lymphotoxin-alfa mutation genotypes were 55.0%, 37.6%, and 7.4% for controls and 42.7%, 46.0%, and 11.3% for coronary disease patients (p = 0.02), respectively. Smoking, dyslipidemia, family history, and lipoprotein(a) and lymphotoxin-alfa mutations in men were independent variables associated with coronary disease. The area under the curve (C-statistic) increased from 0.779 to 0.802 (p<0.05) with the inclusion of lipoprotein(a) and lymphotoxin-alfa mutations in the set of conventional risk factors. CONCLUSIONS: The inclusion of lipoprotein(a) and lymphotoxin-alfa mutations in the set of conventional risk factors showed an additive but small increase in the risk prediction of premature coronary disease.